Migraine evolution after the cessation of CGRP(-receptor) antibody prophylaxis: a prospective, longitudinal cohort study. (April 2022) - Raffaelli, Bianca; Terhart, Maria; Overeem, Lucas Hendrik; Mecklenburg, Jasper; Neeb, Lars; Steinicke, Maureen; Reuter, Uwe
Background: National and international guidelines recommend stopping migraine prophylaxis with CGRP(-receptor) monoclonal antibodies after 6–12 months of successful therapy. In this study, we aimed to analyze the course of migraine for four months after the cessation of CGRP(-receptor) antibodies use. Methods: This longitudinal cohort study included patients with migraine who received a CGRP-(receptor) antibody for ≥8 months before treatment cessation. We analyzed headache data in the four-week period prior to mAb treatment initiation (baseline), in the month before the last mAb injection, in weeks 5–8 and 13–16 after last treatment. Primary endpoint of the study was the change of monthly migraine days from the month before last treatment to weeks 13–16. Secondary endpoints were changes in monthly headache days and monthly days with acute medication use. Results: A total of 62 patients equally distributed between prophylaxis with the CGRP-receptor antibody erenumab and the CGRP antibodies galcanezumab or fremanezumab participated in the study. Patients reported 8.2 ± 6.6 monthly migraine days in the month before last treatment. Monthly migraine days gradually increased to 10.3 ± 6.8 in weeks 5–8 (p = 0.001) and to 12.5 ± 6.6 in weeks 13–16 (p < 0.001) after drug cessation. Monthly migraine days in weeks 13–16 were not different from baseline values (−0.8 ± 5.4; p > 0.999). Monthly headache days and monthly days with acute medication use showed a similar pattern. Conclusions: The cessation of CGRP(-receptor) antibodies migraine prophylaxis was associated with a significant increase of migraine frequency and acute medication intake over time.